Extrapulmonary tuberculosis: A retrospective study in Eastern India based on diagnostic modalities - Anindya Adhikari; Tripti Das; Ashis Sardar; Anuradha Sinha; Arijit Majumdar; Goutam Dey (Wolters Kluwer Medknow Publications, 2023)
Background: The most common site of tubercular infection is lungs, but various extrapulmonary sites also can be affected by tuberculosis (TB). Very few fine-needle aspiration-based studies supplemented by cartridge-based nucleic acid amplification test (CBNAAT) and radiology have been conducted in any center of tribal-based area situated in Eastern India. Materials and Methods: Sixty extrapulmonary TB cases (28 males and 32 females) received during 3 years (May 2018-April 2021) were included in this study. Results: Diagnoses of different extrapulmonary tubercular lesions were: lymphadenitis (n = 27), cold abscess (n = 18), breast abscess (n = 2), epididymitis (n = 4), oral cavity (n = 3), spine, long bone (n = 2 cases each) and fingertip and TB of the penis (n = 1 case each). Forty-six cases were diagnosed by fine-needle aspiration cytology. CBNAAT diagnosed ten cases where the result of aspiration cytology was inconclusive. Radiology directly diagnosed four cases, whereas it helped another seven cases indirectly to clinch the proper diagnosis of extrapulmonary tubercular lesions. Conclusion: Tuberculous lymphadenitis was the most common extrapulmonary lesion. Females outnumber male cases. Aspiration cytology aided by CBNAAT and radiology proved indispensable to diagnose extrapulmonary tubercular lesions, especially for economically constrained persons.